Disaggregating economic micro-data under limited sectoral breakdown - Rosland, Anitha; Abd Rahman, Muhammad Daaniyall; Saari, Mohd Yusof; Utit, Chakrin; Norazman, Umi Zakiah (Fakulti Ekonomi dan Pengurusan, Universiti Putra Malaysia, 2020)
Limited sectoral breakdown or unmatched sectoral details is some of recurring issues in input-output impact assessment analysis. This issue will refrain researchers from obtaining comprehensive and detailed results, which also lead to some valuable information loss and limited policy recommendation. This study examines the robustness of economic microdata disaggregation when a limited sectoral breakdown is available to the data users. Specifically, we test a disaggregation technique on national income and employment survey-based data set namely the Household Income Survey (HIS) 2005 and compute the multiplier indicators for the respective data, using Input Output Table 2005. Our results show that the technique can be used to produce consistent results with some limited caveats to avoid result misinterpretations.